The Global Commonwealth of Citizens Toward Cosmopolitan Democracy - Archibugi, Daniele 1958- (Princeton Univ. Press, 2008)
Contents; Tables and Figures; Acronyms and Abbreviations; Preface and Acknowledgments; Chapter 1 Introduction: A Queen for the World?; PART ONE: THE THEORY OF COSMOPOLITAN DEMOCRACY; Chapter 2 The Conception of Democracy; Chapter 3 Democracy and the Global System; Chapter 4 The Architecture of Cosmopolitan Democracy; Chapter 5 Critical Debate on Cosmopolitan Democracy; PART TWO: THE PRACTICE OF COSMOPOLITAN DEMOCRACY; Chapter 6 The Central Importance of the United Nations; Chapter 7 Cosmopolitanism and Humanitarian Intervention; Chapter 8 Can Democracy Be Exported?
Keywords: Electronic books; Vereinte Nationen; Democracy; Globalization; Humanitarian intervention; International organization; United Nations; World citizenship; Globalisierung; Demokratisierung; Internationalisierung; Nationalstaat; Weltgesellschaft; Weltbürgertum; Demokratie